HAVEN: a hazard avoidance and VEhicular navigation system for autonomous maneuvering in the AREE venus rover - Mukundan, Arvind; Shastri, Bhardwaj; Karmakar, Riya; Gade, Pratham Chandraskhar; Wang, Hsiang-Chen (Frontiers in Mechanical Engineering, 2025)
IntroductionVenus, a celestial entity historically associated with Earth, has a planetary atmosphere characterized as hellish. Throughout the history of space exploration, a finite number of spacecraft have been sent to examine this mysterious planet. Of the many journeys to our celestial satellite, only about twelve have successfully communicated with the planetary surface. The landers with the longest operational lifespans functioned for just a little while, succumbing to the intense and relentless mix of severe heat and pressure. The National Aeronautics and Space Administration’s Jet Propulsion Laboratory (NASA-JPL) is currently evaluating a mission proposal to revisit the planet Venus.MethodsThe Automaton Rover for Extreme Environment (AREE) mission concept aims to perform prolonged exploration of the terrain of our adjacent celestial body, employing wind-powered automatons and mechanical devices, with the objective of functioning for extended durations rather than mere minutes. As the rover navigates the Venusian surface and relays data to an orbiting satellite, it is essential for it to simultaneously detect and recognize any obstacles that could hinder its advancement.ResultsTo facilitate the innovative mission concept of AREE, the primary mechanism utilized for the identification and navigation of perilous situations during the operational lifespan of the prospective rover will be designated as the Hazard Avoidance and VEhicular Navigation System (HAVEN). This research study will concentrate on the design concept of the HAVEN sensor, which seeks to augment the rover’s capabilities by identifying diverse impediments, such as rocks, fissures, and slopes.DiscussionBy accurately detecting and recognizing these challenges, the rover will navigate Venus’s rough terrain and enhance its exploration endeavors, hence enabling the acquisition of significant observational data.